2006
DOI: 10.4310/cag.2006.v14.n5.a8
|View full text |Cite
|
Sign up to set email alerts
|

Heegaard Genus of the Connected Sum of M-small Knots

Abstract: Abstract. We prove that if K 1 ⊂ M 1 , . . . , K n ⊂ M n are m-small knots in closed orientable 3-manifolds then the Heegaard genus of E(# n i=1 K i ) is strictly less than the sum of the Heegaard genera of the E(K i ) (i = 1, . . . , n) if and only if there exists a proper subset I of {1, . . . , n} so that # i∈I K i admits a primitive meridian. This generalizes the main result of Morimoto in [17].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Therefore, for some i, S is isotopic to F i . In Rieck and Kobayashi [13,Proposition 2.13] it was shown that if Σ untelescopes to the essential surface ∪ i F i , then Σ weakly reduces to any connected separating component of ∪ i F i ; therefore Σ weakly reduces to S. This proves the first part of Claim 1.…”
Section: Claimmentioning
confidence: 73%
“…Therefore, for some i, S is isotopic to F i . In Rieck and Kobayashi [13,Proposition 2.13] it was shown that if Σ untelescopes to the essential surface ∪ i F i , then Σ weakly reduces to any connected separating component of ∪ i F i ; therefore Σ weakly reduces to S. This proves the first part of Claim 1.…”
Section: Claimmentioning
confidence: 73%
“…It is well known that E(4 1 ) admits a genus 2 Heegaard splitting. By amalgamating a genus 2 Heegaard splitting for E(4 1 ) with a genus 2 Heegaard splitting of E(3 1 ) ∪ E(L) we obtain a weakly reducible Heegaard splitting of M; by [9] (see also [6,Lemma 2.7] for a more general statement) this Heegaard splitting has genus 3. This establishes the existence of weakly reducible minimal genus Heegaard splittings of M.…”
Section: Proof Of Theoremmentioning
confidence: 99%
“…This bound is given in terms of the bridge number of the branch set with respect to the Heegaard surface for N given in Theorem 1.2, i.e., the projection of the invariant Heegaard surface for M . The definition of bridge number with respect to a Heegaard surface is given in Definition 12.1 (for a detailed discussion see, for example, [12] or [10]). We prove: For proving Theorem 1.1 we study the intersection of strongly irreducible Heegaard surfaces, that is, the intersection of Σ and its image under the involution f (Σ).…”
Section: Theorem 12 (Genus Of Double Covers) Let M Be An Irreduciblmentioning
confidence: 99%